An Optimized Surfactant-Based PEG-PLCL In Situ Gel Formulation For Enhanced Activity Of Rosuvastatin In Poloxamer-Induced Hyperlipidemic Rats - Ahmed TA; Mussari MA; Abdel-Hady SES; El-Say KM (Dove Medical Press, 2019)
Tarek A Ahmed,1,2 Mohammed A Mussari,1 Seham El-Sayed Abdel-Hady,1 Khalid M El-Say1,2 1Department Of Pharmaceutics, Faculty Of Pharmacy, King Abdulaziz University, Jeddah, Kingdom of Saudi Arabia; 2Department Of Pharmaceutics And Industrial Pharmacy, Faculty Of Pharmacy, Al-Azhar University, Cairo 11651, EgyptCorrespondence: Tarek A AhmedDepartment Of Pharmaceutics, Faculty Of Pharmacy, King Abdulaziz University, PO. Box 80200, Jeddah 21589, Kingdom of Saudi ArabiaEmail tabdelnapy@kau.edu.saBackground: Injectable in situ gel (ISG) systems suffer from high initial drug release that may result in toxic effects.Objective: This work aimed to develop an injectable sustained release rosuvastatin (RSV) ISG formulation with minimum initial drug burst and improved hyperlipidemic efficacy.Methods: Six formulation factors that affect RSV release after 0.5, 2 and 24 hrs have been screened and the significant ones were optimized utilizing an experimental design tool. The optimum ISG formulation components were physicochemically characterized. Kinetic treatment, dissolution efficiency and mean dissolution time were investigated for the developed ISG formulations. Pharmacodynamic effects of the optimized ISG formulation were studied and compared to ISG formulation loaded with free RSV and to a marketed oral drug product.Results: The concentration polylactide-co-ϵ-caprolactone (25: 75), the surfactant hydrophilic lipophilic balance (HLB) and the ratio of surfactant to polyethylene glycol 400 were significantly affecting the release of RSV during the first 24 h. Physicochemical characterization demonstrated complete dispersion of RSV in the polymeric matrix with slight changes in the drug crystalline structure. The optimized formulation demonstrated acceptable syringeability, good flow rate and was able to extend the in vitro drug release for 34 days. The ISG formulations complied with Weibull model. Pharmacodynamic study revealed a sustained reduction in the lipid profile that lasted for 21 days with a marked decrease in the lipid level during the first 24 hrs from the ISG system loaded with free RSV.Conclusion: The optimized RSV ISG formulation could be considered a promising strategy due to a reduction in dosing frequency and enhancement in hypolipidemic efficacy.Keywords: hypolipidemic activity, in situ gel, initial burst, optimization, rosuvastatin